Optimization of material requirements to support the accuracy of delivery materials based on quantity of cubicost analysis results - Fandini, Reina Maulidya; Putra, I Nyoman Dita Pahang; Trigunarsyah, Bambang (SINERGI, 2025)
Construction projects heavily rely on labor, materials, and equipment to ensure timely completion, with materials being a significant cost component. This study addresses discrepancies between rebar inventory and material demand, which can disrupt production and delay project completion. This study aims to determine the rebar volume using Cubicost TRB and optimize the lowest requirement cost by applying the Silver-Meal and Wagner-Whitin algorithms. Detailed engineering data supports the application, ensuring rebar bends meet technical standards at beam, column, and slab intersections. Material planning incorporates project schedules, inventory records, and rebar volume data from Cubicost. This planning considered the minimization of ordering and storage costs. The results showed that the volume of rebar calculated using the Cubicost application was more accurate than the project's bill of quantity data. The use of the Cubicost application proved to be more advantageous, resulting in a 1% reduction compared to the project data. Then, the Silver Meal algorithm resulted in total costs that were 21% lower than those of the Wagner-Whitin method in minimizing overall inventory costs, particularly for high-demand rebar types such as D13 and D19. These findings highlight the importance of accurate inventory scheduling and selecting appropriate lot-sizing techniques to minimize costs and prevent delays. Future research can compare Cubicost TRB’s accuracy with other software and extend the Silver-Meal and Wagner-Whitin algorithms to other materials.